Family Development Index (FDI) of rural producers who develop forestry in the Municipality of Peçanha, Minas Gerais, Brazil (Research, Society and Development, 2020)
The aim of the present article was to present the Family Development Index (FDI) of rural producers working with forestry in the municipality of Peçanha, Minas Gerais. The focus was given to two groups of producers identified in the survey, classified as fostered producers and independent producers. The first group stands out for the partnership established with the cellulose industry, through the forestry promotion program for wood production, and the second, for acting independently, whose wood is destined for the production of charcoal, without bond to the cellulose industry. In order to accomplish the demands of the research, bibliographic and documentary research was carried out as well as an incursion into the field. To validate the data, statistical tests were performed to understand the differences found in the two groups of producers. The FDI was the tool used to get to know the reality of the families of the interviewed producers. The results showed that the forested producers have an FDI better than that of the independent producers, which means that the forestry promotion has contributed to the improvement of the producers' quality of life, allowing better health and education conditions for the members of their family. Through the distribution of the producers' FDI in the two groups, the influence of the property size, the forestry area and the development area on the level of development of each producer is verified.